The transformation myth leading your organization through uncertain times - Kane, Gerald C. ca. 20. Jh; Nanda, Rich ca. 20. Jh; Phillips, Anh Nguyen ca. 20. Jh; Copulsky, Jonathan R. (The MIT Press, 2021)
"A practical guide for business leaders to learn from moments of crisis and advance their digital capabilities"--
Keywords: Pandemie; Digitalisierung; COVID-19; Change Management; Führung; Organisation; Crisis management; Organizational change; Information technology / Management